2002
DOI: 10.1007/s00520-001-0319-y
|View full text |Cite
|
Sign up to set email alerts
|

'Enough is enough': qualitative findings on the impact of dexamethasone during reinduction/consolidation for paediatric acute lymphoblastic leukaemia

Abstract: The results of a longitudinal study conducted with children undergoing treatment for acute lymphoblastic leukaemia (ALL) and their families in Brisbane, Australia, indicate that the emotional impact of one of the protocol drugs, dexamethasone, is acutely distressing. The findings presented cover the second interviews with the parents and children of the first 11 ALL families to have completed the re-consolidation stage of treatment. The results indicate that the negative impact of this drug is particularly sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 19 publications
5
43
0
Order By: Relevance
“…Some corticosteroids, such as dexamethasone, were noted to be particularly severe in terms of their side effects. Such findings echo similar insights provided on dexamethosone use in paediatrics [21].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Some corticosteroids, such as dexamethasone, were noted to be particularly severe in terms of their side effects. Such findings echo similar insights provided on dexamethosone use in paediatrics [21].…”
Section: Discussionsupporting
confidence: 90%
“…The research that does exist is comprised of three case studies [5,26,37] and one exploratory empirical study of paediatric leukaemia patients [21]. There is a strong need for empirical data in relation to adults under treatment for haematological malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…Overtiredness has serious impacts on normal life ranging along the continuum from ennui and exhaustion to the more extreme psychiatric condition of paranoia. The findings from the adult data resonate with previous insights from paediatric hematology research on the steroid dexamethasone, where it was found that children were awake all night eating excessively (McGrath & Pitcher, 2002). There is also evidence of sleeplessness being a problem associated with steroid use in an adult case study of a patient undergoing an allogeneic bone marrow transplant (Nakamae et al, 2002).…”
Section: Discussionsupporting
confidence: 86%
“…However, there is a dearth of literature documenting the emotional and psychiatric side effects of steroid use for hematology patients (McGrath, Pun, James, & Holewa, 2007) and a related lack of comprehensive recommendations for the management, education, and support of patients undergoing steroid treatment and their families. The psychosocial research conducted to date is limited to three case studies (Ducore, Waller, Emslie, & Bertolone, 1983;Nakame, Yamane, & Aoyama, 2002;Sutor, Wells, & Rummans, 1996) and one exploratory empirical study of paediatric leukaemia patients (McGrath & Pitcher, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence While children treated with GCs may experience a host of side effects, families often find the emotional and behavioral aberrations caused by steroids to be the most deleterious to quality of life [62]. Several studies have examined the nature and prevalence of the latter phenomenon in children.…”
Section: Review Of the Literaturementioning
confidence: 99%